Evaluasi Kebijakan Jalan Khusus Angkutan Batu Bara dan Tantangan Pelaksanaannya - Liza Fitria Kisnanda (Universitas Djuanda, 2026)
This research is motivated by the urgent need to address the transportation of coal, which still utilizes public roads, resulting in traffic congestion, infrastructure damage, air pollution, and public unrest. This situation indicates that the implementation of the designated special road policy set by the government has not been optimal. The aim of this study is to evaluate the implementation of the special road policy for coal transportation and to identify obstacles in its execution. This research uses a qualitative approach with a case study method. The analysis was conducted using policy evaluation theory, which includes six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results show that the policy has not been implemented effectively and efficiently due to funding limitations and weak coordination among stakeholders. Additionally, aspects of governmental equity and responsiveness remain low. Nevertheless, the policy is considered appropriate in terms of substance; however, its implementation has not been optimal. The conclusion of this study is that the special road policy has not yet achieved its intended goals. Therefore, a policy review and enhanced coordination among relevant parties are necessary. The impact of this research underscores the importance of accelerating the construction of special roads to reduce negative impacts on the community and improve policy effectiveness.